Perceptions on fraud and corruption policies and strategies in public procurement within the Western Cape Provincial Treasury (WCPT) - Opperman, Sophia Kathleen (Stellenbosch : Stellenbosch University, 2015)
Thesis (MPA)--Stellenbosch University, 2014.